Analysis of Performance-Based and Affirmation Grant Management in the Madrasah Reform Program - Fajar Kurniawan (Khazanah Pendidikan Islam, 2025)
This study aims to analyze the management of the Bantuan Kinerja dan Afirmasi (BKBA) within the Madrasah Reform Program initiated by the Ministry of Religious Affairs of the Republic of Indonesia in collaboration with the World Bank to improve the quality of governance and educational services in madrasahs. The study focuses on two madrasahs with distinct characteristics: MIS Assubkiyah in Rawalumbu, Bekasi (urban area) and Jamiyatul Usbuiyah in Pandeglang, Serang (rural area). The research employs a qualitative approach using a comparative case study design. Data were collected through observation, in-depth interviews using purposive sampling techniques, and documentation. The data were then analyzed using Miles and Huberman’s interactive model, supported by source triangulation to ensure validity. The results indicate that BKBA management in both madrasahs covers the aspects of planning, implementation, reporting, and monitoring and evaluation. MIS Assubkiyah demonstrates more effective governance due to stronger human resources, higher digital literacy, and transformational leadership, whereas Jamiyatul Usbuiyah encounters limitations related to facilities and managerial capacity. Internal factors influencing the effectiveness of management include the leadership of the madrasah principal, team commitment, and work culture, while external factors involve assistance from the Ministry of Religious Affairs, technical support, and geographical conditions. The tangible impacts of the BKBA are reflected in the improvement of physical facilities, the modernization of digital learning, and enhanced transparency in financial governance. This study concludes that the effectiveness of BKBA management is strongly influenced by the application of Performance-Based Management principles, which emphasize transparency, accountability, and collective participation. Strengthening mentoring and digital management training is needed to ensure the sustainability of the program and its contribution to improving the quality of Islamic education.